Effects of CPAP on oxidative stress and nitrate efficiency in sleep apnoea: a randomised trial - Alonso-Fernandez, A; Garcia-Rio, F; Arias, M A; Hernanz, A; de la Pena, M; Pierola, J; Barcelo, A; Lopez-Collazo, E; Agusti, A (Thorax, 2009)
Previous studies have presented contradictory data concerning obstructive sleep apnoea syndrome (OSAS), lipid oxidation and nitric oxide (NO) bioavailability. This study was undertaken to (1) compare the concentration of 8-isoprostane and total nitrate and nitrite (NOx) in plasma of middle-aged men with OSAS and no other known co-morbidity and healthy controls of the same age, gender and body mass index; and (2) test the hypothesis that nasal continuous positive airway pressure (CPAP) therapy attenuates oxidative stress and nitrate deficiency. A prospective, randomised, placebo controlled, double-blind, crossover study was performed in 31 consecutive middle-aged men with newly diagnosed OSAS and 15 healthy control subjects. Patients with OSAS were randomised to receive sham CPAP or effective CPAP for 12 weeks. Blood pressure, urinary catecholamine levels and plasma 8-isoprostane and NOx concentrations were obtained before and after both treatment modalities. Patients with OSAS had significantly higher 8-isoprostane levels (median (IQR) 42.5 (29.2-78.2) vs 20.0 (12.5-52.5) pg/ml, p = 0.041, Mann-Whitney test) and lower NOx levels (264 (165-650) vs 590 (251-1465) micromol/l, p = 0.022) than healthy subjects. Body mass index, blood pressure and urinary catecholamines were unchanged by CPAP therapy, but 8-isoprostane concentrations decreased (38.5 (24.2-58.7) pg/ml at baseline vs 22.5 (16.2-35.3) pg/ml on CPAP, p = 0.0001) and NOx levels increased (280 (177-707) vs 1373 (981-1517) micromol/l, p = 0.0001) after CPAP. OSAS is associated with an increase in oxidative stress and a decrease in NOx that is normalised by CPAP therapy.